Sugar transporters: mediators of carbon flow between plants and microbes - Lei, Mengyu; Wang, Xiaodi; Chen, Kuan; Wei, Qianqian; Zhou, Miaomiao; Chen, Gong; Su, Shuai; Tai, Yuying; Zhuang, Kexin; Li, Dexiao; Liu, Mengjuan; Zhang, Senlei; et al. (Frontiers in Plant Science, 2025)
Pathogens and symbiotic microorganisms significantly influence plant growth and crop productivity. Enhancing crop disease resistance and maximizing the beneficial role of symbiotic microorganisms in agriculture constitute critical areas of scientific investigation. A fundamental aspect of plant-microorganisms interactions revolves around nutritional dynamics, characterized by either “food shortage” or “food supply” scenarios. Notably, pathogenic and symbiotic microorganisms predominantly utilize photosynthetic sugars as their primary carbon source during host colonization. This phenomenon has generated substantial interest in the regulatory mechanisms governing sugar transport and redistribution at the plant-microorganism interface. Sugar transporters, which primarily mediate the allocation of sugars to various sink organs, have emerged as crucial players in plant-pathogen interactions and the establishment of beneficial symbiotic associations. This review systematically categorized plant sugar transporters and highlighted their functional significance in mediating plant interactions with pathogenic and beneficial microorganisms. Furthermore, we synthesized recent advancements in understanding the molecular regulatory mechanisms of these transporters and identified key scientific questions warranting further investigation. Elucidating the roles of sugar transporters offers novel strategies for enhancing crop health and productivity, thereby contributing to agricultural sustainability and global food security.